Correlation of magnetic resonance and arthroscopy in the diagnosis of shoulder injury. Issue 10 (25th August 2021) - Groarke, Patrick; Jagernauth, Simond; Peters, Susan E; Manzanero, Silvia; O'Connell, Paul; Cowderoy, Greg; Gilpin, David; Hope, Benjamin; Marchant, Darren; Cutbush, Kenneth; Andrews, Steve; Duke, Phillip FR; et al.
Abstract: Background: Advances in shoulder magnetic resonance imaging (MRI) and arthrography (MRA) have revolutionised musculoskeletal diagnosis and surgical planning. Despite this, the overall accuracy of MRI, with or without intra‐articular contrast, can be variable. Methods: In this prospective non‐randomised analysis, 200 participants (74.5% males) with suspected shoulder injuries underwent MRI (41.0%) or MRA followed by arthroscopy. A study specific proforma was developed to ensure consistency of reporting by radiologists and surgeons. The reports were compared to assess the predictive power of MRI/MRA. Specific assessment of rotator cuff tendon appearance, long head of biceps (LHB) tendon appearance, position and anchor, subacromial space, glenoid labrum and humeral cartilage grade were included. Results: Shoulder MRA demonstrated a higher agreement with arthroscopy than MRI for supraspinatus, infraspinatus and subscapularis tendon appearance (κ = 0.77 vs. κ = 0.61, κ = 0.55 vs. κ = 0.53 and κ = 0.58 vs. κ = 0.46 respectively). There were also superior agreement rates with MRA compared to MRI for LHB tendon appearance (κ = 0.70 vs. κ =0.54) and position (κ = 0.89 vs. κ = 0.72). As an overall assessor of shoulder pathology we found significantly higher total agreement scores when MRA was used ( p  = 0.002). Discussion: Whilst magnetic resonance imaging with arthrography is an extremely useful tool to assess underlying pathological shoulder states it does not confer 100% accuracy. In cases whereby this modality is inconclusive, an examination under anaesthesia and diagnostic arthroscopic assessment for the detection of intra‐articular shoulder pathology may be considered. Abstract : Our study indicated both MRI and MRA conferred substantial agreement with shoulder arthroscopy for assessment of supraspinatus, LHB tendon position, labral pathology and humeral cartilage assessment. MRA however, demonstrated a higher agreement with arthroscopy than MRI for supraspinatus, infraspinatus and subscapularis tendon appearance. MR imaging is an excellent modality to assess shoulder pathology that can be further enhanced with the addition of arthrography.